Evaluasi Kinerja Standar Pelayanan Terminal Penumpang Tipe A Banda Aceh Menggunakan Importance Performance Analysis dan Customer Satisfaction Index - Yusputri, Rafiqa Muhnita; Muhammad Rizki; Heru Pramanda; Febrina Dian Kurniasari; Bunyamin Bunyamin (Universitas Iskandar Muda, 2026)
The increasing number of passengers at the Banda Aceh Type A Passenger Terminal requires improvements in service performance to enhance passenger satisfaction. This study aimed to evaluate the terminal service performance based on passenger importance and satisfaction levels and to determine the Customer Satisfaction Index (CSI). A quantitative approach was employed using questionnaires distributed to 100 respondents selected through simple random sampling. The evaluation referred to the Indonesian Minister of Transportation Regulation No. PM 40 of 2015, covering six service aspects: safety, security, reliability, comfort, convenience, and equality. Data were analyzed using descriptive statistics, Importance Performance Analysis (IPA), and CSI. The results indicate that the main service attributes requiring improvement are road safety facilities, fire extinguishers, driver rest areas, and battery charging facilities. The CSI value of 84.62% indicates that passengers are very satisfied with the overall service performance of the Banda Aceh Type A Passenger Terminal.